Survey Minat Siswa terhadap Pembelajaran Sepak Takraw pada Siswa Kelas VII di SMP Negeri Diwek - Synthiawati, Novita Nur; Hendrawan, Kahan Tony (SPRINTER: Jurnal Ilmu Olahraga, 2024)
This study aims to determine students' interest in sepak takraw game, research with survey method with descriptif approach, Population 95 students of class VII SMPN Diwek, sampling with “Total Sampling” that every existing population is considered as a sample, instrument with questionnaire and to analyse data with descriptive analysis and percentage. On indicators of general knowledge in the medium category (78.95%), internal indicators in the medium category (65.26%). indicators of external factors in the medium category (57.89%). To conclude that student interest is in the medium category.